Systematic Review Protocols: Interventions Used to Manage Patients Undergoing Hematopoietic Stem Cell Transplantantion - Hutton, Brian; Yazdi, Fatemeh; Wolfe, Dianna; Allan, David; Chris, Bredeson; Cameron, Bill; Cowan, Juthaporn; Moher, David (Université d'Ottawa | University of Ottawa, 2015)
Background. Allogeneic hematopoietic cell transplantation (HSCT) represents a multi-faceted and complex health care intervention that can be lifesaving for patients with hematologic cancers, other serious blood or immune disorders, and inherited metabolic conditions. Optimization of strategies to improve patient outcomes has evolved gradually as transplant activity has increased globally over the past 25 years. With increasing activity, it is now possible to address questions regarding drug effectiveness and safety in HSCT using available evidence from randomized controlled trials. To date, however, clear recommendations regarding treatment selection within an array of transplant-related interventions remains lacking. In particular, it remains challenging to quantify the strength of evidence that underpins many treatment and prevention strategies used currently by transplant centres. This is due to a lack of direct or indirect comparisons for particular interventions, and has led to wide variation in institutional protocols for many aspects of care in HSCT. Research Gaps. While some systematic reviews and guidance have been published on specific interventions for HSCT, there have been no comprehensive efforts to establish guidelines based on networks of evidence and formal network meta-analyses of randomized trials. In particular, the literature is currently lacking analyses of indirect comparisons that include important effectiveness and safety outcomes. These comparisons can be achieved through network meta-analysis and would be transformative for transplant physicians, their patients, and funding bodies. Research Plan. We plan to conduct a series of three systematic reviews addressing the following research questions: 1.What are the relative safety and effectiveness of competing conditioning regimens (and groupings of conditioning regimens) used for allogeneic HSCT? 2.What are the relative safety and effectiveness of different pharmacologic strategies to prevent and treat graft versus host disease following allogeneic HSCT? 3.What are the relative safety and effectiveness of different drugs used to prevent and treat bacterial, viral, and fungal infections following allogeneic HSCT? Each review is anticipated to incorporate network meta-analyses for comparison of multiple interventions of clinical relevance to clinicians treating patients undergoing allogeneic HSCT.
Keywords: Allogeneic; Conditioning; GVHD; Hematopoietic Stem Cell Transplant; Infection; Prophylaxis; Treatment